Singapore's principled and balanced approach to the Israel-Palestine conflict - Mohamed Nassir (2023)
Singapore’s resilience is being tested once again, this time by the current Israel-Hamas war. Internally, the war has the potential to create fissures between the communities, while externally, over-zealous politicians in Muslim-majority countries around Singapore denounce it for its purported support of Israel. Singapore’s response to the current Israel-Hamas war however, as has always been the case, is based on a principled and balanced approach.